Single-cell transcriptome reveals potential mechanisms for gout in children - Yu, Shengyou; Qi, Ren; Xiao, Liang; Huang, YiHui; Yu, Li (Frontiers in Immunology, 2025)
ObjectivePediatric gout is a condition that differs from traditional adult gout and has attracted significant attention. This study aims to explore the molecular mechanisms underlying pediatric gout.MethodsWe analyzed peripheral blood samples from pediatric gout patients and healthy controls using single-cell RNA sequencing (scRNA-seq). Statistical tests were employed to analyze the data and identify significant differences between the groups.ResultsOur findings revealed that CD14+ monocytes and DN T cells play crucial roles in pediatric gout. CD14+ monocytes are essential for recognizing and phagocytosing monosodium urate (MSU) crystals, triggering inflammation. DN T cells may be involved in the adaptive immune response within gouty joints. These cells not only contribute to the inflammatory response but also interact with other immune cells, amplifying the inflammatory cascade. Comparative analysis with adult gout studies highlighted both similarities and differences in cellular and molecular mechanisms between children and adults. The CD14+ monocytes may be interact with other immune cells through the TNF-α/NF-κB signaling pathway. Targeting this pathway may offer therapeutic potential for managing pediatric gout.ConclusionThe results provide a foundation for new diagnostic markers and therapeutic targets for pediatric gout. They also pave the way for future research and the development of targeted therapies that can effectively manage and potentially prevent the debilitating effects of gout in children. Understanding the unique molecular mechanisms in pediatric gout could influence treatment strategies and improve patient outcomes.